Psychological Distress and Attitudes Toward Seeking Professional Psychological Help among Transwomen in Indonesia - Tandias, Evelyn; Shanti, Theresia Indira (Jurnal Psikologi, 2024)
Transwomen are one of the minority groups in Indonesia vulnerable to a high level of psychological distress. The level of psychological distress can indicate the need to seek psychological help. The most basic component of seeking help is attitude. Without a positive attitude, individuals are less likely to have the intention of seeking help and do seeking help. This study aimed to investigate the level of psychological distress, attitudes toward seeking professional psychological help, and the relationship between symptoms of psychological distress with attitudes toward seeking professional psychological help in 117 samples of transwomen in Indonesia. Results indicated that 72% of participants were classified as having a high level of psychological distress. A negative association between anxiety symptoms and psychological openness indicated that the more symptoms of anxiety that participants were experiencing, the less likely they were to open up about their psychological problems.